Cover Feature: Sulfur/Nitrogen Co‐Doped In‐Plane Porous Carbon Nanosheets as Superior Anode of Potassium‐Ion Batteries (Batteries & Supercaps 5/2022). Issue 5 (6th April 2022) - Li, Guilan; Xu, Anding; Zhong, Fulan; Huang, Chuyun; Sun, Hao; Xu, Zhiguang; Wu, Songping; Yan, Yurong
Abstract : The Cover Feature shows porous carbon nanosheets with fishnet‐like microstructures, featuring excellent potassium‐ion storage capacity as anodes for potassium‐ion batteries, possessing great potential for powering the future city. More information can be found in the Research Article by S. Wu, Y. Yan and co‐workers .